2019
DOI: 10.1523/jneurosci.2395-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of CC2D1A Reduces Hippocampal Synaptic Plasticity and Impairs Cognitive Function through Rac1 Hyperactivation

Abstract: Coiled-coil and C2 domain containing 1A (CC2D1A) is an evolutionarily conserved protein, originally identified as a nuclear factor-B activator through a large-scale screen of human genes. Mutations in the human Cc2d1a gene result in autosomal recessive nonsyndromic intellectual disability. It remains unclear, however, how Cc2d1a mutation leads to alterations in brain function. Here, we have taken advantage of Cre/loxP recombinase-based strategy to conditionally delete Cc2d1a exclusively from excitatory neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 68 publications
(99 reference statements)
2
26
0
Order By: Relevance
“…Since RAC1 activity is enhanced by sumoylation, hyperactived RAC1 results in abnormal dendritic morphology and synaptic dysfunction. Remarkably, pharmacological blockade of RAC1 activity partially rescues deficits in synaptic plasticity and memory observed in Cc2d1a-cKO mice (Yang et al, 2019). In conclusion, this work provides further experimental evidence supporting the hypothesis that aberrant sumoylation is a key molecular determinant underlying ID etiology.…”
Section: Cc2d1-dependent Non-syndromic Idsupporting
confidence: 75%
See 2 more Smart Citations
“…Since RAC1 activity is enhanced by sumoylation, hyperactived RAC1 results in abnormal dendritic morphology and synaptic dysfunction. Remarkably, pharmacological blockade of RAC1 activity partially rescues deficits in synaptic plasticity and memory observed in Cc2d1a-cKO mice (Yang et al, 2019). In conclusion, this work provides further experimental evidence supporting the hypothesis that aberrant sumoylation is a key molecular determinant underlying ID etiology.…”
Section: Cc2d1-dependent Non-syndromic Idsupporting
confidence: 75%
“…Mutations in the Coiled-coil and C2 domain containing 1A (CC2D1A) gene are associated with non-syndromic ID (OMIM 608443). This gene codes for CC2D1A, a DNA binding protein that regulates multiple cellular signaling pathways, including serotonin and dopamine receptors, dendritic arborization, synapse maturation, and plasticity (Zhao et al, 2011;Al-Tawashi et al, 2012;Manzini et al, 2014;Oaks et al, 2017;Yang et al, 2019). Consistent with these roles, the loss of CC2D1A in vivo determines the appearance of cognitive and social deficits (Oaks et al, 2017).…”
Section: Cc2d1-dependent Non-syndromic Idmentioning
confidence: 99%
See 1 more Smart Citation
“…The impetus for developing a novel digging paradigm originated from previous studies of a mouse model for ID and ASD, where the Cc2d1a gene is conditionally removed in the cortex and hippocampus, the Cc2d1a cKO (Oaks et al, 2017;Yang et al, 2019). While these mice showed hyperactivity and obsessive grooming in addition to cognitive and social deficits (Oaks et al, 2017;Yang et al, 2019), reduced digging activity was identified in the marble burying test with no change in marble number (Oaks et al, 2017). We found the DBD test to be more sensitive in defining digging changes with a decrease in burrowing and a trend towards increased exploratory digging in male cKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Global loss of Cc2d1a in the mouse does not appear to grossly affect development, but causes early postnatal lethality through respiratory and swallowing deficits (Oaks et al, 2017;Zhao, Li, & Chen, 2010;Zhao, Raingo, Chen, & Kavalali, 2011). Postnatal removal of Cc2d1a in the forebrain, bypasses early lethality and behavioral analysis in male mice recapitulates several features of ASD and ID including cognitive and social deficits, hyperactivity, increased anxiety-like behaviors and obsessive grooming (Oaks et al, 2017;Yang, Yu, Wen, Ling, & Hsu, 2019 -Tawashi et al, 2012) and cAMP response element-binding protein (CREB), a transcription factor critical for spatial memory formation ( Figure 3) (Alberini, 2009;Kandel, 2012;Ortega-Martínez, 2015;Sekeres, Neve, Frankland, & Josselyn, 2010).…”
Section: Cc2d1amentioning
confidence: 99%